The Hospital Microbiome Project: Meeting report for the 2nd Hospital Microbiome Project, Chicago, USA, January 15th, 2013. Issue 3 (May 2013) - Shogan, Benjamin; Smith, Daniel; Packman, Aaron; Kelley, Scott; Landon, Emily; Bhangar, Seema; Vora, Gary; Jones, Rachael; Keegan, Kevin; Stephens, Brent; Ramos, Tiffanie; Kirkup, Benjamin; et al.
Abstract This report details the outcome of the 2nd Hospital Microbiome Project workshop held on January 15th at the University of Chicago, USA. This workshop was the final planning meeting prior to the start of the Hospital Microbiome Project, an investigation to measure and characterize the development of a microbial community within a newly built hospital at the University of Chicago. The main goals of this workshop were to bring together experts in various disciplines to discuss the potential hurdles facing the implementation of the project, and to allow brainstorming of potential synergistic project opportunities.